An unexpected Amish Christmas - Good, Rachel J. (Zebra book., 2021)
Recovering from a horse and buggy accident that took the lives of his family, Jacob Zook is struggling to regain both his spirit and his body. While his legs remain stubbornly opposed to moving, he exercises his hands by writing, and finds the perfect outlet for his grief in inspirational letters to the Amish newspaper. When Keturah Esch, a woman who works at the Green Valley Farmer's Market, responds with gratitude, Jacob has no idea that his hardship is about to become a blessing...Dealing with her own loss, and responsible for her three siblings, Keturah's new correspondence with the anonymous letter writer becomes a source of joy. And when a shy young man confined to a wheelchair begins to visit the market, Keturah is happy to make his acquaintance--never knowing that Jacob is afraid to reveal himself as her pen pal. After all, what can he offer her, when he can't even walk? Can faith bring two lonely people together in perfect union? As Christmas approaches, Jacob and Keturah get a chance to make their gifts to each other worthy of the blessing of love...